Notary's Authority in Making Deeds Related to the Takeover of Collateral (AYDA) as an Alternative for Resolving Bad Credit - Agustina, Saptarina Dian; Sri Darmadi, Nanang (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2023)
This research aims to analyze: 1) The authority of notaries in the Notary Position Law (UUJN) regarding the making of collateral takeover deeds (AYDA) as an alternative for resolving bad credit. 2) Procedures that must be followed by notaries in assisting in resolving bad debts through AYDA. The approach used in this research is the statutory approach. This type of research is normative legal research. The type and source of data in this research is secondary data. obtained by literature study. The analysis in this research is prescriptive. The results of the research are concluded: 1) The authority of a notary in the Notary Position Law (UUJN) is related to making a collateral takeover deed (AYDA) as an alternative for resolving bad credit, namely making authentic deeds to transfer collateral belonging to customers who receive facilities. The bank must legally have a legal basis for the transfer of collateral. The deeds made by the Notary in the implementation of AYDA are the Deed of Sale and Purchase Agreement, the Deed of Authorization to Sell, and the Deed of Settlement Agreement for problematic financing with the voluntary delivery of collateral. Notaries also play a role in the process of changing the name of collateral, PPJB, and matters relating to Mortgage Rights (SKMHT and APHT), carrying out the roya process for objects to be mortgaged at the National Land Agency, to ensure that the collateral objects are not bound by any agreement. For the process of selling collateral through an auction at the State Property and Auction Services Office, hereinafter referred to as KPKNL, the notary acts as a Class II Auction Officer as the official who makes the Deed of Auction Minutes. In connection with the implementation of AYDA in banking, of course there is still a need for a notary as an official who has the authority to make authentic deeds as per their authority in Article 15 UUJN. 2) The procedures that must be followed by notaries in assisting in resolving bad debts through AYDA are examining documents and information, verifying ownership and authority, coordinating between related parties, preparing legal deeds, registering and archiving documents and providing legal certainty. Notaries have the responsibility to ensure that the process of resolving bad debts and making deeds occurs in accordance with applicable law. This includes ensuring the validity of documents and clarity of the legal processes involved.